Correlation of Antibiotic Resistance with Sepsis Incidence, Hospital Mortality, and Time of Sepsis Onset in Community Acquired Bacterial Pneumonia - Kresentia Anita Raniputri; Harsini Harsini; Leli Saptawati; Reviono Reviono (Jurnal Respirologi Indonesia, 2022)
Background: Community acquired pneumonia is associated with high morbidity and mortality. Treatment of multidrug-resistant organisms (MDRO) infection in pneumonia is a challenge. Antibiotic resistance is a major factor determining clinical treatment unresponsiveness and rapid progression to sepsis. Septic patients with MDRO have a higher hospital mortality. The correlation of antibiotic resistance with the incidence of sepsis and hospital mortality is yet to be known. This study analyzed the correlation of antibiotic resistance with sepsis incidence, hospital mortality, and time of sepsis onset.Methods: Retrospective cohort study of patients with community acquired bacterial pneumonia from July-December 2019 at RSUD Dr. Moewardi. The correlation between antibiotic resistance and incidence of sepsis, hospital mortality was tested by using Chi Square and Fisher's exact test correction. Association between two variables with relative risk. Survival analysis and log rank test were used to examine the time differences of sepsis onset.Results: There was a correlation between antibiotic resistance and incidence of sepsis in community acquired bacterial pneumonia (r = 0.417, p = 0.000) with RR = 4,294 (95% CI 2,886-6,390). The median time of sepsis onset was day 0 in the MDRO group and day 4 in non-MDRO group (p = 0.000).Conclusion: There is a correlation between antibiotic resistance and incidence of sepsis in community acquired bacterial pneumonia with a fairly strong and significant correlation value. The presence of antibiotic resistance increases the incidence of sepsis fourfold. Antibiotic resistance also affects the time of sepsis onset.